Four-week habituation to simulated barefoot running improves running economy when compared with shod running - Warne, J. P.; Warrington, G. D. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The purpose of this study was to evaluate the effects of a 4-week familiarization to simulated barefoot running (SBR) on running economy (RE) when compared with shod running. Fifteen trained male runners (age: 24 ± 4 years; stature: 177.2 ± 6.21 cm; mass: 67.99 ± 7.36 kg and VO2max 70.2 ± 5.2 mL/kg/min) were recruited. Subjects completed two RE tests, 24 h apart, in a random order, in both the SBR and shod condition (pretest) at 11 km/h and 13 km/h. Oxygen uptake, heart rate, stride frequency, and foot strike patterns were measured in both conditions. Subjects then completed a 4-week familiarization period of SBR, before repeating the two RE tests (post-test). At pretest, there was no significant difference in RE between SBR and shod running (P = 0.463), but following the 4-week familiarization period, RE significantly improved by 6.9% in the SBR condition compared with shod running (46.4 ± 0.9 vs 43.2 ± 1.2 mL/kg/min; P = 0.011). A significant improvement in RE was observed in the SBR condition (8.09%) between the pretest and post-test (47.0 ± 1.2 vs 43.2 ± 1.2 mL/kg/min; P = 0.002). RE improved in the SBR condition as a result of familiarization, and became significantly lower in SBR compared with shod running.